Classification Learning Effectiveness of Living with Contextual Teaching and Learning (CTL) and Cooperative Learning (CL) Type Group Investigation (GI) (Universitas Negeri Semarang, 2019)
The result of questionnaire given to 256 students of class VII of SMP Negeri 37 Semarang obtained information that motivation, scientific attitude, and cognitive learning result is still low. One of the teaching models can be used to solve these problems is the CTL and CL GI type models, because it links knowledge to real-world situations and emphasizes maximum student engagement. The purpose of this study is to analyze the effectiveness of classification of living creatures with CTL and CL type GI model of motivation, scientific attitude, response and student cognitive learning outcomes. The research design is Pretes-Posttest Control Group Design. Motivation, student response is analyzed by likert scale. Mastery Test is used to analyze the completeness of cognitive learning outcomes. One-way anova test is used to test three average differences. The results showed that motivation and scientific attitude are in good category. The calculation of experimental class 1 and experiment 2 respectively which stated by KKM is 84,38% and 81,25%. F count> F table (16.086> 3.094), then Ho is rejected, so it can be concluded that there is a difference between the average postes value of experiment class 1, experiment class 2, and control. Learning CTL and CL type GI received a very positive and positive response.